Sonification of numerical data for education. (2nd January 2019) - Vines, Karen; Hughes, Chris; Alexander, Laura; Calvert, Carol; Colwell, Chetz; Holmes, Hilary; Kotecki, Claire; Parks, Kaela; Pearson, Victoria
ABSTRACT: Sonification is the use of non-speech audio to convey information. In this article, sonifications are representations of plots aimed at improving the accessibility of teaching materials. The electronic nature of sonifications means that they can be deployed to students via teaching interfaces such as virtual learning environments. We describe a two-phase study that explores sonifications of plots as a teaching tool in the context of distance learning in STEM. The overall objective of these two phases was to begin to assess the suitability of audio versions of graphs as a teaching tool for non-sighted and sighted students. In the first phase the effectiveness of sonifications within a small group of participants who took part in activities like those encountered in a distance learning setting was explored. We found that even though sonifications were new to them, participants were able to use them to gain impressions of the corresponding plots. The second phase deployed sonifications to all students on an Open University (OU) module. Although many of the students who chose to respond did so negatively, some found the sonifications an interesting augmentation of the plot. Overall, we demonstrate that for a subset of students, information in a plot can be communicated using sonifications.